Disaster Risk Reduction (DRR) Model in Senior High School: A Comparison of Tsunami Affected and Unaffected Areas in Banda Aceh City - Tasya Salsabila; Sulastri; Budi Arianto (MultiTech Publisher, 2025)
This study aims to analyze the implementation of the disaster Risk Reduction (DRR) model in Senior High School in Banda Aceh City in schools located in areas affected and unaffacted by the tsunami in 2024. This paper uses a qualitative approach with a comparative study design, the research was conducted through a group investigation method in four schools. The research explores students’ knowledge of DRR, including disaster experience, disaster information, participation in disaster activities, and understanding when a disaster occurs. Through the group investigation model, the research addressed the differences between schools in tsunami-affected and unaffacted areas. The result show that tsunami-affected schools have higher understanding and preparedness related to disaster risk reduction than unaffected schools, with differences in training participation and information sources.